ANALISIS STRATEGI PEMASARAN PADA PENGRAJIN SARUNG TENUN DI SAMARINDA - Jeniati Paladan; Rahayu, Vitria Puri; Sutrisno (Jurnal Prospek: Pendidikan Ilmu Sosial dan Ekonomi, 2024)
This research aims to determine the application of the marketing mix strategy in the Samarinda Woven Sarong business. This research uses qualitative descriptive research, by collecting data through interviews with craftsmen or owners of Samarinda woven sarong businesses. Based on the results of research and discussion, it shows that the implementation of the 4P marketing mix strategy (Product, Price, Promotion, Place). In the Woven Sarong Business. The use of market places and social media such as Shopee, Instagram, Facebook, WhatsApp as promotional strategies as well as distribution locations is based on customer orders, especially in the production of clothing types. The most prominent products are related to color design, where craftsmen use light colors that are trending, This received a positive response from customers.